Rare earth modified Co-based alloy / ceramic composite coating and preparation method thereof

By adding NbC powder and rare earth powder to the Co-based alloy, a rare earth-modified Co-based alloy/ceramic composite coating is prepared, which solves the problem of insufficient comprehensive performance of anti-wear, cavitation and corrosion resistance in the prior art, and achieves efficient anti-wear, cavitation and corrosion resistance of the coating.

CN119530793APending Publication Date: 2025-02-28CHINA YANGTZE POWER
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411791456.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The prior art lacks comprehensive performance in terms of abrasion resistance, cavitation resistance and corrosion resistance. When conventional rare earth modified coatings improve their abrasion resistance, their cavitation resistance will decrease and their corrosion resistance will not be ideal.

Method used

The hardness, cavitation resistance, abrasion resistance and corrosion resistance of the coating are improved by adding NbC powder and rare earth powder to the Co-based alloy.

Benefits of technology

The anti-wear performance of the overflow components of the turbine is achieved by 3-6 times, the anti-cavitation performance is increased by 2-5 times, and the corrosion resistance of neutral salt spray is greater than 480h, which significantly improves the overall performance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a rare earth modified Co-based alloy / ceramic composite coating and a preparation method thereof. The rare earth modified Co-based alloy / ceramic composite coating is prepared from the following raw materials in percentage by mass: 20-35 wt% of NbC powder, 0.05-0.1 wt% of rare earth powder and the balance of Co-based alloy powder, wherein the rare earth powder is composed of 40-60 wt% of Nd2O3 powder and 40-60 wt% of Y2O3 powder, and the Co-based alloy powder is composed of the following raw materials of, by atomic percent, 28-35 at% of Cr powder, 0.5-1 at% of Mo powder, 4-7 at% of C powder, 1-3 at% of Fe powder, 1-3 at% of Ni powder, 1-2 at% of W powder and the balance Co powder. The NbC powder and the rare earth powder are added into the Co-based alloy, so that the hardness, cavitation erosion resistance, abrasion resistance and corrosion resistance of the composite coating are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of alloy / ceramic composite coatings, and in particular relates to a rare earth modified Co-based alloy / ceramic composite coating and a preparation method thereof. Background Art

[0002] In the field of hydropower generation, the abrasion damage of turbines has always been a difficult problem in the operation of hydropower stations. Under the combined effects of cavitation and sediment wear, the surface morphology of flow-through components such as turbine guide vanes and runners changes, destroying the proper flow conditions for water flow around the flow-through components, affecting the output and operating efficiency of the turbine; in addition, the material damage caused by abrasion can lead to the failure of flow-through components, and in severe cases, the unit will produce strong vibration, noise and load fluctuations, directly affecting the safety, stability and service life of the turbine. Especially in watersheds with high head and high sand content, the abrasion damage of turbines is particularly serious, and the maintenance cycle has to be shortened, and even "water is abandoned to save the machine" is forced to be used during the flood season, causing great economic losses and energy waste. Therefore, it is very urgent to solve the problems of abrasion and cavitation of flow-through components of turbines.

[0003] At present, the main measures to resist abrasion and cavitation include optimizing the design of turbine flow parts, selecting stainless steel with good abrasion and cavitation resistance as the material of flow parts, using anti-abrasion coating to protect the surface of flow parts, and reducing the sand content of water flow through sand reduction facilities. Among them, developing anti-abrasion and cavitation coating is the most economical and effective method.

[0004] At present, the most widely used anti-wear coating is hard coating, which is mainly made of metal materials, including carbides and other hard phase metal ceramics, hard wear-resistant alloys and self-fluxing alloys, etc. It has strong wear resistance and can effectively resist the wear and cavitation damage of hard particles. And with the development of high-performance surface protective coating materials and preparation technology, high-entropy alloy / ceramic composite coating prepared by laser cladding has become a new trend in the development of high-quality surface technology.

[0005] Chinese patent CN118389924A discloses a rare earth modified reinforced toughening composite wear-resistant and cavitation-resistant coating powder, a coating and a preparation method thereof. The coating powder is composed of WC powder, Co powder, Cr powder, rare earth, and reinforced toughening powder, wherein the rare earth is CeO, and the reinforced toughening powder is one or more of NbC and VC. The coating is modified by using rare earth and reinforced toughening powder, which effectively improves the comprehensive properties of the coating such as density, wear resistance and cavitation resistance, and solves the problem of coating performance degradation due to abrasion and cavitation problems of flow-through parts of hydraulic equipment such as turbines and pumps.

[0006] Chinese patent CN114214555B discloses a cavitation-resistant and corrosion-resistant metal-ceramic matrix composite material and its preparation method, which uses metal materials, ceramic materials and rare earth materials as raw materials, and is prepared by laser remelting process to obtain a cavitation-resistant and corrosion-resistant metal-ceramic matrix composite material, wherein the metal material includes metal Ni, metal Co, metal Cr, Ni-based alloy, Co-based alloy, Cr-based alloy, Ti-based alloy, duplex stainless steel, aluminum bronze or nickel aluminum bronze, the ceramic material is carbide ceramic and / or oxide ceramic, and the rare earth material includes rare earth element single substance or rare earth element compound, specifically cerium oxide or lanthanum oxide. The prepared composite material can be used for various flow-through parts, such as rudders, propellers, turbine blades, etc., greatly reducing the maintenance frequency of parts due to cavitation and corrosion damage, improving the use efficiency of equipment, and extending the service life of equipment.

[0007] However, the existing technology is slightly insufficient in terms of comprehensive performance in terms of cavitation resistance, abrasion resistance and corrosion resistance. 2 and / or La 2 O 3 When modified with rare earth powder, the composite coating has a tendency to decrease in anti-cavitation performance as its anti-abrasion performance improves, and the prepared coating often has unsatisfactory anti-corrosion performance. Therefore, it is necessary to develop a composite coating that has good anti-abrasion performance, anti-cavitation performance, and anti-corrosion performance to meet the needs of different fields. Summary of the invention

[0008] In view of the above technical problems, the present invention provides a rare earth modified Co-based alloy / ceramic composite coating and a preparation method thereof, wherein NbC powder and rare earth powder are added to the Co-based alloy to improve the hardness, cavitation resistance, abrasion resistance and corrosion resistance of the composite coating.

[0009] In order to achieve the above object, the present invention provides a rare earth modified Co-based alloy / ceramic composite coating, which is composed of the following raw materials in mass percentage: 20-35 wt% NbC powder, 0.05-0.1 wt% rare earth powder, and the balance Co-based alloy powder.

[0010] Preferably, the rare earth powder is composed of 40-60 wt% Nd 2 O 3 powder and 40-60 wt% Y 2 O 3 Powder composition.

[0011] Further preferably, the Nd 2 O 3 The particle size is 1-5μm, Y 2 O 3 The particle size is 1-5μm.

[0012] Preferably, the Co-based alloy powder is composed of the following raw materials in atomic percentage: Cr powder: 28-35 at%, Mo powder: 0.5-1 at%, C powder: 4-7 at%, Fe powder: 1-3 at%, Ni powder: 1-3 at%, W powder: 1-2 at%, and the balance is Co powder.

[0013] Preferably, the particle size of the Co-based alloy powder is 10-105 μm.

[0014] Preferably, the particle size of the NbC powder is 1-5 μm.

[0015] Further preferably, the Co-based alloy powder, NbC powder and rare earth powder are prepared by gas atomization.

[0016] A method for preparing a rare earth modified Co-based alloy / ceramic composite coating comprises the following steps: (1) Co powder, Cr powder, Mo powder, C powder, Fe powder, Ni powder and W powder are mixed according to atomic percentage to obtain Co-based alloy powder; (2) mixing the Co-based alloy powder, NbC powder and rare earth powder according to mass percentage to obtain a Co-based alloy / ceramic composite coating powder; (3) Laying the rare earth modified Co-based alloy / ceramic composite powder separately and drying it; (4) Clean the substrate and dry it; (5) The dried rare earth modified Co-based alloy / ceramic is laser clad to prepare a rare earth modified Co-based alloy / ceramic composite coating.

[0017] Preferably, the paving thickness in step (3) is ≤8 cm, the drying temperature is 80-100° C., and the drying time is 1-5 h.

[0018] Preferably, the cleaning method in step (4) is cleaning with an organic solvent, and the drying temperature is 50-60°C.

[0019] Preferably, the process parameters of the laser cladding in step (5) are: spot diameter of 4-6 mm, laser power of 2.5-4 kW, overlap rate of 40%-60%, cladding head scanning speed of 5-20 mm / s, and powder feeding rate of 15-90 g / min.

[0020] Preferably, the thickness of the prepared rare earth modified Co-based alloy / ceramic composite coating is 0.5-10 mm.

[0021] Preferably, the substrate in step (4) is any one of Q235 steel, ZG06Cr13Ni5Mo stainless steel and 316L stainless steel.

[0022] The beneficial effects of the present invention are: 1. Co-based alloy is prepared by mixing Co powder, Cr powder, Mo powder, C powder, Fe powder, Ni powder and W powder. The multi-element eutectic forms a special atomic structure of a single solid solution or a simple eutectic structure, which has high hardness and high toughness, and synergistically improves the alloy's anti-wear, anti-cavitation and anti-corrosion properties. At the same time, C powder and W powder form WC, which is dispersed in the microstructure of steel and can withstand greater pressure and friction during wear, protecting the steel matrix, thereby improving the alloy's wear resistance and hardness.

[0023] 2. Mix Co-based alloy and NbC powder and prepare composite coating by laser cladding method. Co-based alloy powder and NbC work synergistically to increase the thermal hardness, thermal shock resistance and thermal oxidation resistance of the coating. By adding rare earth Nd 2 O 3 and Y 2 O 3 Rare earth, Nd 2 O 3 and Y 2 O 3 It is distributed in the Co phase and at the grain boundaries of WC grains in the alloy, increasing the wettability of Co to WC grains; inhibiting the uneven growth of WC grains and refining the grains; inhibiting the formation of η phase in the alloy; and improving the wear resistance and corrosion resistance of the alloy.

[0024] 3. The rare earth modified Co-based alloy / ceramic composite coating prepared by the present invention can increase the hardness of the commonly used base material ZG05Cr13Ni5Mo of the turbine by about 25-35%, improve the anti-abrasion performance by 3-6 times, and improve the anti-cavitation performance by 2-5 times; the neutral salt spray corrosion resistance time is greater than 480h.

[0025] 4. The present invention has high production efficiency and is more suitable for small space construction compared to supersonic thermal spraying technology. It can prepare thicker coatings to solve the problems of abrasion, cavitation and corrosion on the surface of turbines. DETAILED DESCRIPTION

[0026] The technical solution of the present invention is further explained below in conjunction with specific embodiments. It is worth noting that the following embodiments are only preferred embodiments of the present invention and should not be construed as limiting the present invention. The protection scope of the present invention shall be subject to the contents recorded in the claims. Any modification or replacement made by a person skilled in the art to the technical solution of the present invention without creative work shall fall within the protection scope of the present invention.

[0027] The Cr powder, Mo powder, C powder, Fe powder, Ni powder, W powder, Co powder, NbC powder, Y2 O 3 Powder, Nd 2 O 3 The powders were prepared by gas atomization. The particle size of Cr powder, Mo powder, C powder, Fe powder, Ni powder, W powder and Co powder was 80 μm, and that of NbC powder, Y 2 O 3 Powder and Nd 2 O 3 The particle size of the powder is 3 μm.

[0028] Example 1 (1) Preparation of Co-based alloy powder: Cr powder: 31 at%, Mo powder: 0.9 at%, C powder: 4.5 at%, Fe powder: 2 at%, Ni powder: 1.7 at%, W powder: 1.2 at% according to the atomic ratio, and the balance is Co powder, and mechanically mix to obtain Co-based alloy powder; (2) Preparation of Co-based alloy / ceramic composite coating powder: According to the mass percentage, NbC powder: 21 wt%, rare earth powder: 0.05 wt%, and the remainder is Co-based alloy powder, and mechanical mixing is performed to prepare Co-based alloy / ceramic composite coating powder, wherein the rare earth powder is 50 wt% Y 2 O 3 powder and 50 wt % Nd 2 O 3 Powder composition; (3) Drying: Spread the Co-based alloy / ceramic composite coating powder to a thickness of 8 cm and dry it at 90 °C for 4 h; (4) Substrate pretreatment: spray anhydrous ethanol solution onto the surface of the substrate, clean it and dry it at 50°C; the substrate is ZG06Cr13Ni5Mo stainless steel; (5) Laser cladding: The dried Co-based alloy / ceramic composite coating powder is coated on the surface of the substrate by laser cladding process, wherein the process parameters of laser cladding are: spot diameter: 4.2 mm, laser power: 2.5 KW, overlap rate: 50%, cladding head scanning speed: 8 mm / s, powder feeding rate: 20 g / min.

[0029] Example 2 (1) Preparation of Co-based alloy powder: Cr powder: 35 at%, Mo powder: 1 at%, C powder: 5.4 at%, Fe powder: 3 at%, Ni powder: 2.5 at%, W powder: 1.6 at% according to the atomic ratio, and the balance is Co powder, and mechanically mix to obtain Co-based alloy powder; (2) Preparation of Co-based alloy / ceramic composite coating powder: Take NbC powder: 30 wt%, rare earth powder: 0.08 wt%, and the remainder is Co-based alloy powder according to mass percentage, and mechanically mix to prepare Co-based alloy / ceramic composite coating powder, wherein the rare earth powder is 50 wt% Y 2 O 3 powder and 50 wt% Nd 2 O 3 Powder composition; (3) Drying: Spread the Co-based alloy / ceramic composite coating powder to a thickness of 8 cm and dry it at 90 °C for 4 h; (4) Substrate pretreatment: spray anhydrous ethanol solution onto the surface of the substrate, clean it and dry it at 50°C; the substrate is ZG06Cr13Ni5Mo stainless steel; (5) Laser cladding: The dried Co-based alloy / ceramic composite coating powder is coated on the surface of the substrate by laser cladding process, wherein the process parameters of laser cladding are: spot diameter: 4.2 mm, laser power: 3.2 KW, overlap rate: 50%, cladding head scanning speed: 10 mm / s, powder feeding rate: 20 g / min.

[0030] Example 3 (1) Preparation of Co-based alloy powder: Cr powder: 28 at%, Mo powder: 0.5 at%, C powder: 6.8 at%, Fe powder: 1 at%, Ni powder: 1 at%, W powder: 1.8 at% according to the atomic ratio, and the balance is Co powder, and mechanically mix to obtain Co-based alloy powder; (2) Preparation of Co-based alloy / ceramic composite coating powder: Take NbC powder: 35 wt%, rare earth powder: 0.1 wt%, and the remainder is Co-based alloy powder, and mechanically mix to prepare Co-based alloy / ceramic composite coating powder, wherein the rare earth powder is 50 wt% Y 2 O 3 powder and 50 wt% Nd 2 O 3 Powder composition; (3) Drying: Spread the Co-based alloy / ceramic composite coating powder to a thickness of 8 cm and dry it at 90 °C for 4 h; (4) Substrate pretreatment: spray anhydrous ethanol solution onto the surface of the substrate, clean it and dry it at 50°C; the substrate is ZG06Cr13Ni5Mo stainless steel; (5) Laser cladding: The dried Co-based alloy / ceramic composite coating powder is coated on the surface of the substrate by laser cladding process, wherein the process parameters of laser cladding are: spot diameter: 4.2 mm, laser power: 2.6 KW, overlap rate: 50%, cladding head scanning speed: 12 mm / s, powder feeding rate: 20 g / min.

[0031] Example 4 (1) Preparation of Co-based alloy powder: Cr powder: 28 at%, Mo powder: 0.5 at%, C powder: 4 at%, Fe powder: 1 at%, Ni powder: 1 at%, W powder: 2 at% according to the atomic ratio, and the balance is Co powder, and mechanically mix to obtain Co-based alloy powder; (2) Preparation of Co-based alloy / ceramic composite coating powder: According to the mass percentage, NbC powder: 25 wt%, rare earth powder: 0.06 wt%, and the rest is Co-based alloy powder, and mechanically mixed to prepare Co-based alloy / ceramic composite coating powder, wherein the rare earth powder is 40 wt% Y 2 O 3 powder and 60 wt% Nd 2 O 3 Powder composition; (3) Drying: Spread the Co-based alloy / ceramic composite coating powder to a thickness of 6 cm and dry it at 80 °C for 5 h; (4) Substrate pretreatment: spray anhydrous acetone solution onto the surface of the substrate, clean it and dry it at 55°C; the substrate is ZG06Cr13Ni5Mo stainless steel; (5) Laser cladding: The dried Co-based alloy / ceramic composite coating powder is coated on the surface of the substrate by laser cladding process, wherein the process parameters of laser cladding are: spot diameter: 5 mm, laser power: 4 kW, overlap rate: 40%, cladding head scanning speed: 5 mm / s, powder feeding rate: 15 g / min.

[0032] Example 5 (1) Preparation of Co-based alloy powder: Cr powder: 35 at%, Mo powder: 1 at%, C powder: 5.4 at%, Fe powder: 3 at%, Ni powder: 3 at%, W powder: 1 at% according to the atomic ratio, and the balance is Co powder, and mechanically mix to obtain Co-based alloy powder; (2) Preparation of Co-based alloy / ceramic composite coating powder: According to the mass percentage, NbC powder: 32wt%, rare earth powder: 0.09wt%, and the remainder is Co-based alloy powder, and mechanical mixing is performed to prepare Co-based alloy / ceramic composite coating powder, wherein the rare earth powder is 60wt% Y 2 O 3powder and 40 wt% Nd 2 O 3 Powder composition; (3) Drying: Spread the Co-based alloy / ceramic composite coating powder flat to a thickness of 2 cm and dry it at 100 °C for 1 h; (4) Substrate pretreatment: spray anhydrous acetone solution onto the surface of the substrate, clean it and dry it at 60°C; the substrate is ZG06Cr13Ni5Mo stainless steel; (5) Laser cladding: The dried Co-based alloy / ceramic composite coating powder is coated on the surface of the substrate by laser cladding process, wherein the process parameters of laser cladding are: spot diameter: 6 mm, laser power: 3.6 KW, overlap rate: 60%, cladding head scanning speed: 20 mm / s, powder feeding rate: 90 g / min.

[0033] Comparative Example 1 (1) Preparation of Co-based alloy powder: Cr powder: 28 at%, Mo powder: 0.5 at%, Fe powder: 1 at%, Ni powder: 1 at% and the remainder is Co powder to prepare Co-based alloy powder according to the atomic ratio; (2) Drying: Spread the Co-based alloy powder to a thickness of 8 cm and dry it at 90 °C for 4 h; (3) Substrate pretreatment: spray anhydrous ethanol solution onto the surface of the substrate, clean it and dry it at 50°C; the substrate is ZG06Cr13Ni5Mo stainless steel; (4) Laser cladding: The dried Co-based alloy / ceramic composite coating powder is coated on the surface of the substrate by laser cladding process, wherein the process parameters of laser cladding are: spot diameter: 4.2 mm, laser power: 2.6 KW, overlap rate: 50%, cladding head scanning speed: 12 mm / s, powder feeding rate: 20 g / min.

[0034] Comparative Example 2 The method and steps are the same as those in Example 1, except that the amount of NbC powder is changed to 18 wt % to prepare a Co-based alloy / ceramic composite coating.

[0035] Comparative Example 3 The method and steps are the same as those in Example 1, except that the amount of NbC powder is changed to 37wt% to prepare a Co-based alloy / ceramic composite coating.

[0036] Comparative Example 4 The method and steps are the same as those of Example 3, except that the NbC powder in step (2) is omitted, and the Co-based alloy powder prepared in step (1) is directly used to prepare the Co-based alloy / ceramic composite coating.

[0037] Comparative Example 5 The method and steps are the same as those in Example 1, except that no rare earth powder is added to the Co-based alloy / ceramic composite coating powder to prepare the Co-based alloy / ceramic composite coating.

[0038] Comparative Example 6 The method and steps are the same as those in Example 1, except that the amount of rare earth powder in step (2) is changed to 0.15wt%, to prepare a Co-based alloy / ceramic composite coating.

[0039] Comparative Example 7 The method and steps are the same as those in Example 1, except that the rare earth powder in step (2) is replaced with pure Y 2 O 3 Powder, to prepare Co-based alloy / ceramic composite coating.

[0040] Comparative Example 8 The method and steps are the same as those in Example 1, except that the rare earth powder formula in step (2) is changed to 20 wt% Y 2 O 3 powder and 80wt% Nd 2 O 3 Powder composition.

[0041] Comparative Example 9 The method and steps are the same as those of Example 1, except that the rare earth powder formula in step (2) is changed to consist of 50 wt % Nd powder and 50 wt % Y powder.

[0042] Result detection: The composite coating prepared in the above embodiment and comparative example 1 was taken, and its hardness was tested according to the method of GB / T 4340.1-2009 "Vickers hardness test for metallic materials - Part 1: Test method", and its anti-abrasion and anti-cavitation properties were tested according to the method of SL / T 815-2021 "Technical specification for abrasion protection of water pumps", and its anti-corrosion performance was tested according to GB / T 10125. The specific results are shown in Table 1: Table 1 Properties of composite coatings

[0043] Note: The multiples in the anti-abrasion performance and anti-cavitation performance are based on the anti-abrasion performance and anti-cavitation performance of the ZG06Cr13Ni5Mo substrate being 1.

[0044] The results show that: it can be seen from Examples 1-5 that the coating has a higher hardness through the ratio of raw materials, and at the same time has higher anti-abrasion performance, anti-cavitation performance, and excellent corrosion resistance.

Claims

1. A rare earth modified Co-based alloy / ceramic composite coating, characterized in that: The invention is composed of the following raw materials in percentage by weight: 20-35 wt% of NbC powder, 0.05-0.1 wt% of rare earth powder, and the balance of Co-based alloy powder.

2. The rare earth modified Co-based alloy / ceramic composite coating according to claim 1, characterized in that: The rare earth powder consists of 40-60 wt% of Nd2O3 powder and 40-60 wt% of Y2O3 powder.

3. A rare earth modified Co-based alloy / ceramic composite coating according to claim 2, characterized in that: The particle size of Nd2O3 is 1-5 μm, and the particle size of Y2O3 is 1-5 μm.

4. The rare earth modified Co-based alloy / ceramic composite coating according to claim 1, characterized in that: The Co-based alloy powder is composed of the following raw materials in atomic percentage: Cr powder: 28-35 at%, Mo powder: 0.5-1 at%, C powder: 4-7 at%, Fe powder: 1-3 at%, Ni powder: 1-3 at%, W powder: 1-2 at%, and the balance is Co powder.

5. The rare earth modified Co-based alloy / ceramic composite coating according to claim 1, characterized in that: The particle size of the Co-based alloy powder is 10-105 μm.

6. The rare earth modified Co-based alloy / ceramic composite coating according to claim 1, characterized in that: The particle size of the NbC powder is 1-5 μm.

7. A method for preparing a rare earth modified Co-based alloy / ceramic composite coating according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Co powder, Cr powder, Mo powder, C powder, Fe powder, Ni powder and W powder are mixed according to atomic percentage to obtain Co-based alloy powder; (2) mixing Co-based alloy powder, NbC powder and rare earth powder according to mass percentage to obtain Co-based alloy / ceramic composite coating powder; (3) Separately lay the rare earth modified Co-based alloy / ceramic composite powders and lay them flat for drying; (4) Clean the substrate and dry it; (5) Preparation of rare earth modified Co-based alloy / ceramic composite coating by laser cladding.

8. The preparation method according to claim 7, characterized in that: The paving thickness in step (3) is ≤8 cm, the drying temperature is 80-100° C., and the drying time is 1-5 h.

9. The preparation method according to claim 7, characterized in that: The cleaning method described in step (4) is organic solvent cleaning, and the drying temperature is 50-60°C.

10. The preparation method according to claim 7, characterized in that: The process parameters of the laser cladding in step (5) are: spot diameter of 4-6 mm, laser power of 2.5-4 kW, overlap rate of 40%-60%, scanning speed of cladding head of 5-20 mm / s, powder feeding rate of 15-90 g / min.

Citation Information

Patent Citations

  • A cavitation-resistant and corrosion-resistant metal-ceramic matrix composite material and its preparation method

    CN114214555B

  • Rare earth modified reinforced toughened composite wear-resistant cavitation-resistant coating powder, coating and preparation method of rare earth modified reinforced toughened composite wear-resistant cavitation-resistant coating powder

    CN118389924A